2023
DOI: 10.1123/ijsnem.2022-0132
|View full text |Cite
|
Sign up to set email alerts
|

Fasting Before Evening Exercise Reduces Net Energy Intake and Increases Fat Oxidation, but Impairs Performance in Healthy Males and Females

Abstract: Acute morning fasted exercise may create a greater negative 24-hr energy balance than the same exercise performed after a meal, but research exploring fasted evening exercise is limited. This study assessed the effects of 7-hr fasting before evening exercise on energy intake, metabolism, and performance. Sixteen healthy males and females (n = 8 each) completed two randomized, counterbalanced trials. Participants consumed a standardized breakfast (08:30) and lunch (11:30). Two hours before exercise (16:30), par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Therefore, the lower TBM during fasting is acute if not associated with a negative energy balance [ 8 , 10 , 14 , 15 ]. However, the same sample size with different morphological profiles can have different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the lower TBM during fasting is acute if not associated with a negative energy balance [ 8 , 10 , 14 , 15 ]. However, the same sample size with different morphological profiles can have different results.…”
Section: Discussionmentioning
confidence: 99%
“…In eutrophic individuals, this strategy can decrease the TBM by 2% within a few weeks [ 6 ]. Such a lower TBM may result from behavioral and physiological changes that regulate appetite and result in lower caloric intake in the hours of fasting [ 7 ] that is not compensated in the non-restricted feeding period [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Slater et al [ 11 ] found that fasting before evening exercise was associated with reduced motivation and exercise enjoyment. Furthermore, Naharudin et al [ 10 ] and Stratton et al [ 7 ] identified a reduction in general disposition and poor mood in fasting conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Naharudin et al [ 9 ] discovered that fasting reduces the maximum number of repetitions (MNR) acutely performed in the back squat during the fasting state (10–13 h overnight) in trained individuals who skipped breakfast. Some studies identified bad mood and reduction in general disposition, motivation and exercised enjoyment in training in fasting conditions [ 7 , 10 , 11 ]. Diminished levels of blood glucose and increased cortisol levels may be considered the main factors contributing to the negative affective state and the decrease in overall mood and pleasure experienced during physical exercise while fasting [ 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation